2016
DOI: 10.1097/yco.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for clinical applications of rest-activity rhythms in detecting and preventing mood disorders

Abstract: Purpose of review Rest-activity rhythm (RAR) measurements may aid in the detection of depression risk and serve as an important target for depression prevention. This review evaluates the strength of current evidence supporting these potential applications. Recent findings Depression is associated with lower activity levels, that is less regularly patterned, and potentially shifted earlier or later in the day. Specific RAR patterns (combinations of several RAR characteristics) in patients with clinical depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…HAMD is positively correlated with all three RCS band-collapsed measures, negatively correlated with F and IS, and positively correlated with IV. These are all consistent with previous findings, where increased variability from a stable circadian mean have been found to be associated with increased depression [23]. It is interesting to note that, out of the large number of RAR parameters investigated, LF had the highest estimated correlation with HAMD at 31%.…”
Section: Associations With Other Variablessupporting
confidence: 92%
See 2 more Smart Citations
“…HAMD is positively correlated with all three RCS band-collapsed measures, negatively correlated with F and IS, and positively correlated with IV. These are all consistent with previous findings, where increased variability from a stable circadian mean have been found to be associated with increased depression [23]. It is interesting to note that, out of the large number of RAR parameters investigated, LF had the highest estimated correlation with HAMD at 31%.…”
Section: Associations With Other Variablessupporting
confidence: 92%
“…An estimated 300 million people globally suffer from depression [30], making it the leading cause of disability worldwide. Evidence suggests that RARs not only serve as a biobehavioral marker for depression, but more importantly, they represent a risk factor and a potential target for prevention [23]. We consider a study conducted at the University of Pittsburgh to better understand depression symptoms in adults.…”
Section: Motivating Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence supports that disturbances in the 24-h activity rhythm not only are apparent during the depressive episode, but might also precede depressive episodes or may persist afterwards [49]. A recent UK Biobank study suggested a lower relative amplitude in those with a retrospectively determined lifetime incidence of major depressive disorder, bipolar disorder, and mood instability [21•].…”
Section: Depressionmentioning
confidence: 99%
“…Actigraphy has been a mainstay of sleep research since the late 1970s [10] and been used for the analysis of circadian and rest-activity rhythms (RAR) in healthy and specialty populations [11][12][13][14][15][16]. Specifically, actigraph devices detect body movement and sum these movements into digital activity counts across a predetermined epoch interval.…”
Section: Actigraphymentioning
confidence: 99%